At Opposite Poles: Canada's and Norway's approaches to security in the Arctic. Issue 1 (2nd January 2018) - Østhagen, Andreas; Levi Sharp, Gregory; Sigurd Hilde, Paal
Abstract: Canada and Norway are similar in many ways. They share a strong commitment to international law and humanitarian issues, consistently rank amongst the most developed countries in the world, and have aligned themselves with the United States on security matters. They are also two of the five Arctic coastal states that have most actively engaged in northern issues over the last decade. Yet, on the issue of security in the Arctic, their interests have historically differed. This difference came to the fore during the governments of Stephen Harper (2006–2015) and Jens Stoltenberg (2005–2013). This article compares the divergent approaches to security and national defence in Canada and Norway under the Harper and Stoltenberg governments. It asks what role traditional military concerns in the circumpolar region had for the two countries during the period, and how threat perceptions in Ottawa and Oslo shaped their respective Arctic policies. We argue that, to understand the contrasting approaches to Arctic security, two factors are key: (1) the inherent difference in the two countries' approach to, and utilisation of, NATO as a defence alliance; and (2) a clear difference in the role the Arctic holds for security considerations in the two countries given their disparate geographic locations. Ultimately, we make the case that to understand the different approaches adopted by Canada and Norway during the period examined, the Arctic needs to be understood not as one uniform region, but instead as a series of sub-regions where the dominant security variable – Russia – is present to a greater or lesser degree.